Mindfulness Improves Emotion Regulation and Executive Control on Bereaved Individuals: An fMRI Study - Huang, Feng-Ying; Hsu, Ai-Ling; Hsu, Li-Ming; Tsai, Jaw-Shiun; Huang, Chih-Mao; Chao, Yi-Ping; Hwang, Tzung-Jeng; Wu, Changwei W. (Frontiers in Human Neuroscience, 2019)
The grief of bereavement is recognized as a severe psychosocial stressor that can trigger a variety of mental and physical disorders, and the long-lasting unresolved grief has detrimental effect on the brain functionality. Literature has documented the Mindfulness-Based Cognitive Therapy (MBCT) as an efficient treatment for improving the well-being, specifically to the mood and cognition, in general populations. However, little attention has been devoted to neural mechanisms with regard to bereaved individuals’ cognition after MBCT intervention. In this study, we recruited 23 bereaved participants who lost a significant relative within 6 months to 4 years to attend 8-week MBCT course. We used self-reporting questionnaires to measure emotion regulation and functional Magnetic Resonance Imaging (fMRI) with the numerical Stroop task to evaluate the MBCT effect on executive control among the bereaved participants. The self-reported questionnaires showed improvements on mindfulness and reductions on grief, difficulties of emotion regulation, anxiety, and depression after the MBCT intervention. The fMRI analysis demonstrated two scenarios: (1) the activity of the fronto-parietal network slightly declined accompanied with significant improvements on the reaction time of incongruent trials; (2) the activities in posterior cingulate cortex and thalamus were positively associated with Texas Revised Inventory of Grief, implying emotional interferences on cognitive functions. Results indicated that MBCT facilitated the executive control function by alleviating the emotional interferences over the cognitive functions and suggested that the eight-week MBCT intervention significantly improved both executive control and emotion regulations in bereaved individuals.